The Impact of Integrated Community-Based Management of Respiratory Infections in Reducing Child Mortality: Integrated Community-Based Management of Respiratory Infections in Reducing Mortality - Hayat, Babar; Pervaiz, Shumaila; Khan, Zarmast; Zaidi, Syed Hammad Ali; Masood, Ayesha; Sherazi, Sajid Hussain; Khan, Akram Ali (Pakistan Journal of Health Sciences, 2024)
Pneumonia alone is reported to be the leading reason for child death especially within developing countries which have inadequate health care facilities. So, it is necessary to assess the effect of Integrated Community Based Management interventions in reducing the child mortality rate caused by respiratory diseases. Objectives: To assess the effectiveness of early intervention to raise public awareness, ensure that individuals adhere to their treatments and use community health workers to decrease mortality in Low- and middle-income countries and to identify the key factors that contribute to success. Methods: The articles which are purely research articles were retrieved from databases including PubMed, Science Direct, Nature Journal and Google Scholar from January 2013 to April 2024. Peer-reviewed papers published on the management of respiratory diseases in the communities including youngsters below the age of 5 years were included from Africa, South Asia, America and Europe. Only those studies that met the identified criteria for methodological quality, and reporting on the outcomes of interventions and decrease in mortality were considered for inclusion. Results: The findings showed that community health workers played a significant role in the early diagnosis and prevention of respiratory tract disorders and other harmful diseases. There was a significant reduction of 30% in mortalities of infants and preschoolers in communities where the implementation of interventions was made necessary. Conclusions: It was concluded that the implementation of integrated community-based management of respiratory infection is a viable approach used to address child mortality in low-income areas and raise public awareness.